2010
DOI: 10.1111/j.1365-2915.2010.00905.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Established and emerging pathogens inIxodes ricinusticks collected from birds on a conservation island in the Baltic Sea

Abstract: Tick-borne pathogens such as Lyme borreliosis spirochaetes, Anaplasma phagocytophilum, Rickettsia spp. and Babesia spp. cause a great variety of diseases in animals and humans. Although their importance with respect to emerging human diseases is increasing, many issues about their ecology are still unclear. In spring 2007, 191 Ixodes ricinus (Acari: Ixodidae) ticks were collected from 99 birds of 11 species on a bird conservation island in the Baltic Sea in order to test them for Borrelia spp., A. phagocytophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…The low prevalence (0.4%) of A. phagocytophilum in birdfeeding ticks in the present study corresponds to the data from other studies (Franke et al 2010a, Palomar et al 2012. It is also in correspondence with our previous studies that showed 0.9% prevalence of A. phagocytophilum in I. ricinus ticks collected from the vegetation in the area near Kabli and Pulgoja bird stations (Katargina et al 2012).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The low prevalence (0.4%) of A. phagocytophilum in birdfeeding ticks in the present study corresponds to the data from other studies (Franke et al 2010a, Palomar et al 2012. It is also in correspondence with our previous studies that showed 0.9% prevalence of A. phagocytophilum in I. ricinus ticks collected from the vegetation in the area near Kabli and Pulgoja bird stations (Katargina et al 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Birds can carry ticks infected by such tick-borne pathogens as tick-borne encephalitis virus (TBEV) (Waldenstrom et al 2007), Anaplasma phagocytophilum (Alekseev et al 2001, Bjoersdorff et al 2001, Daniels et al 2002, Franke et al 2010a and Borrelia burgdorferi sensu lato (s.l.) (Olsen et al 1995, Gylfe et al 2000, Hanincova et al 2003b, Poupon et al 2006, Franke et al 2010a.…”
mentioning
confidence: 99%
“…Birds, particularly blackbirds, seem to be a pivotal element for the conjunction of the transmission cycles of different tick-borne pathogens. In a recent study, we also found coinfected ticks on other bird species, e.g., European robins (13).…”
Section: Discussionmentioning
confidence: 97%
“…Some small mammals, like meadow voles and chipmunks, develop a strong rickettsemia which might allow transmission to parasitizing ticks (38). Although a vehicle function of birds is hypothesized (13), further investigations are needed to ascertain their possible role as reservoir hosts for SFG rickettsiae.…”
mentioning
confidence: 99%
“…Because small mammals are reservoir hosts for Ba. microti and birds might also be reservoir competent (Siń ski et al 2006, Franke et al 2010), they presumably are major tick hosts in the areas of Karlshagen and Bansin. Nevertheless, further studies are necessary to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%